2020
DOI: 10.1111/tid.13257
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of infectious complications in elderly kidney transplant recipients receiving induction with anti‐thymocyte globulin vs basiliximab

Abstract: Background: Elderly transplant recipients experience lower rates of acute rejection with higher rates of infectious complications compared to their younger counterparts. While less intensive immunosuppression may be preferable, there are no recommendations for depleting versus non-depleting induction strategies. We sought to compare infectious complications between anti-thymocyte globulin (ATG) and basiliximab (IL2RA) induction in elderly kidney transplant recipients (KTRs). Methods:We reviewed 146 KTRs ≥65 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…However, a significantly higher proportion of ATG-induced patients were CMV-positive, which indicated that the patients induced by ATG were at higher risk of CMV infection. Our findings agreed with those reported previously in elderly kidney transplant patients [ 11 ]. On the contrary, some studies have reported no significant effect of induction therapies on CMV incidence in renal transplant patients [ 12 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, a significantly higher proportion of ATG-induced patients were CMV-positive, which indicated that the patients induced by ATG were at higher risk of CMV infection. Our findings agreed with those reported previously in elderly kidney transplant patients [ 11 ]. On the contrary, some studies have reported no significant effect of induction therapies on CMV incidence in renal transplant patients [ 12 ].…”
Section: Discussionsupporting
confidence: 94%
“…Since the early spring of 2020, ATG use in kidney transplantation was significantly reduced, based mostly on previous reports about the increased risk of infectious complications, including death, in ATG-treated patients [ 20 22 ]. Importantly, a recent study confirmed that a higher ATG dosage in high-risk patients is associated with an increased risk of cytomegalovirus disease and death [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the tissues in elderly individuals are fragile and weak, and blood supply and tissue healing are known to worsen with age. Past reports have indicated older age as a risk factor for infectious complications in a variety of diseases [18][19][20]. Postoperative infectious complications lead to longer duration of hospitalization, higher medical costs, and, in the elderly, reduced activities of daily living [21].…”
Section: Discussionmentioning
confidence: 99%